Prostate Specific Antigen Is An Indicator of Prostate Cancer Improvement at Dharmais Cancer Hospital: Literature Review and Secondary Data - Brian Sri Prahastuti; Hestiana Peni Siti Irmanti; Lilis Mis Heri Cicih (Jurnal Ilmiah Kesehatan, 2026)
Prostate cancer is the second leading cause of death in men globally. There were more than 1.4 million new cases and 397,000 deaths in 2022. In Indonesia, prostate cancer ranked fifth with 13,130 new cases and 4,860 deaths. Prostate Specific Antigen (PSA) has been used as a biomarker for detection, therapy evaluation, and prognosis, but its use in Indonesia remains limited. This study aims to examine the role of PSA as an indicator of prostate cancer improvement. The method used was a literature review and secondary data description. Medical records of 70 prostate cancer patients at Dharmais Cancer Hospital in 2024 were collected. Six international publications were identified, demonstrating the consistent use of PSA as an indicator. Responses to not only hormonal therapy but also metabolic adjuvant therapy (Ahn et al., 2020), screening of high-risk populations (Elizabeth K et al., 2021), PSA diagnostic biomarkers and combinations with modern imaging technology (Williams et al., 2022), indicators of therapy response in mCRPC patients (Chi et al., 2023), early indicators of clinical improvement (Biró et al., 2024), PSA is relevant for monitoring multimodal therapy with long-term impact (Kawase et al., 2024). At Dharmais Hospital, 47 patients (67.1%) showed improvement in PSA values, while 23 patients (32.9%) did not experience improvement. Thus, PSA can be implemented in all hospitals with prostate cancer patients as evidenced by scientific publications, and has been implemented at Dharmais Hospital, which is a national cancer referral. Six publications prove PSA to be a reliable indicator of prostate cancer improvement. Therefore, it is recommended that PSA be adopted in clinical practice, supported by financing policies as BPJS benefits, and further research to improve the accuracy of prediction and the quality of prostate cancer management.